Student Diversity and Challenges of Inclusion in Higher Education in India - Sabharwal, Nidhi S.; Malish, C.M. (International Higher Education, 2017)
With an enrollment of 34 million students and a gross enrollment ratio passing 24 percent in 2016, India is in a stage of massification. This article addresses challenges surrounding the issue of growing student diversity on higher education campuses.